ANALISA RISIKO DAN POTENSI REGULASI ANTI-TRUST UNTUK SHARING PLATFORM AIRBNB - Angterina; David Tan; Lu Sudirman (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The Airbnb sharing platform represents a digital accommodation business model that provides affordable lodging alternatives to users worldwide. The existence of the Airbnb platform can increase income for property owners and boost the economy. However, in Indonesia, there is currently no clear anti-trust regulation governing the Airbnb sharing platform, which poses risks that could threaten conventional businesses. This study aims to analyze the risks and potential for anti-trust regulation in Indonesia concerning the Airbnb sharing platform. Utilizing a normative legal research methodology, this study employs both legislative and conceptual approaches, relying on secondary data obtained through library research, with qualitative data analysis to examine relevant Indonesian anti-trust regulations for the Airbnb sharing platform. The findings indicate that anti-trust regulations could effectively govern the Airbnb sharing platform, minimizing risks and ensuring healthy digital competition while fostering strong innovation in digital accommodation services, ultimately creating a competitive digital business landscape.